Ecology of ecosystem services: a case study of riparian systems - Rojas, Isabel M. (Henry Stewart Talks, 2022)
The millennium ecosystem assessment, Ecosystem services, Riparian ecosystems, Bundle of ecosystem services, Trade-offs among ecosystem services, Enhancing ecosystem services, How ecosystem services and conservation goals can be complementary